2007
DOI: 10.1016/s0079-6123(06)65013-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization and state-dependent mechanisms for respiratory rhythm and pattern generation

Abstract: The brainstem respiratory network can operate in multiple functional states engaging different statedependent neural mechanisms. These mechanisms were studied in the in situ perfused rat brainstemspinal cord preparation using sequential brainstem transections and administration of riluzole, a pharmacological blocker of persistent sodium current (I NaP ). Dramatic transformations in the rhythmogenic mechanisms and respiratory motor pattern were observed after removal of the pons and subsequent medullary transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
201
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(213 citation statements)
references
References 44 publications
11
201
0
1
Order By: Relevance
“…Characterization of the typical firing behavior of single neurons with respect to the respiratory cycle has been central to models of respiratory rhythm generation (Molkov et al 2010;Rubin et al 2009;Rybak et al 2007;Smith et al 2007). Categorization of this behavior into different types has provided the substrate for understanding rhythmogenesis as arising from antagonistic pools of neurons with characteristic firing patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of the typical firing behavior of single neurons with respect to the respiratory cycle has been central to models of respiratory rhythm generation (Molkov et al 2010;Rubin et al 2009;Rybak et al 2007;Smith et al 2007). Categorization of this behavior into different types has provided the substrate for understanding rhythmogenesis as arising from antagonistic pools of neurons with characteristic firing patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In the respiratory and locomotor networks, catalogs of 5-20 different firing patterns and their hypothesized connections have been incorporated into increasingly complex models of rhythm generation with the idea that they can potentially explain how these networks generate rhythmicity (Molkov et al 2010;Ogilvie et al 1992;Rubin et al 2009;Rybak et al 1997aRybak et al , 1997bRybak et al , 1997cRybak et al , 2007Rybak et al , 2008Sherwood et al 2011;Smith et al 2007). Yet, despite the reliance of current models on the concept of different physiological categories, the quantitative basis for these categories has not been rigorously established, nor have the criteria that specify inclusion into one or another cell class been described in detail.…”
mentioning
confidence: 99%
“…Configuration and reconfiguration of the in vitro network activity in the tilted transversal slice Recent studies showed that the integrity of the pontomedullary respiratory network is required to generate the eupnoeic three-phasic motor pattern (inspiration, postinspiration, late expiration) of breathing [15,23,24]. Neverthe-less, specific compartments, which particularly include the pre-BötC, maintain their rhythmic activity in vitro [26], and such rhythmic slice preparations were extensively used to study cellular mechanisms of the primary respiratory-like rhythm generation.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…Thus, excitatory drive to the RTN/pFRG would fit to a chemoreceptor-induced increase of the inspiratory rate. Finally, recently published data from the perfused brainstem preparation of juvenile rats suggest that the interaction between the neuronal population of the RTN/pFRG and pre-BötC relate to the inspiratory ramp pattern generator [3,15,23,24,54,55]. This is also supported by the presence of excitatory drive from the preinspiratory-like to the inspiratory-like neuron populations of the pre-BötC, because the excitatory coupling of preinspiratory neurones to augmenting inspiratory neurones is indeed a hallmark for the initiation of the inspiratory ramp in hypothetical models of respiratory rhythm generation [3,23,24,[54][55][56].…”
Section: Technical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation